2010
DOI: 10.1161/circep.110.958116
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Electroanatomic Abnormalities in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background-The diagnostic reliability and pathophysiologic relevance of different noninvasive diagnostic criteria for arrhythmogenic right ventricular cardiomyopathy (ARVC) are undefined. We tested the association between noninvasive diagnostic criteria for ARVC and the presence of low-voltage areas (LVAs) detected at electroanatomic voltage mapping (EAM). Methods and Results-Noninvasive diagnostic criteria, including ECG, signal-averaged ECG (SAECG), and cardiac magnetic resonance (CMR) criteria, were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…Previous studies demonstrated that a fibrofatty ventricular scar can be visualized as RV DCE in approximately one third to one half of ARVC patients. 16,31,34 Tandri et al 31 first reported RV DCE in 8 (67%) of 12 of patients with ARVC and demonstrated its relation to inducibility of sustained monomorphic VT at electrophysiological testing and fibrofatty myocardial changes at EMB. Sen-Chowdhry et al 16 reported unequivocal RV DCE in 13 (65%) of 20 patients who fulfilled task force diagnostic criteria for ARVC and were desmosomal gene mutation carriers.…”
Section: Rv Dce Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that a fibrofatty ventricular scar can be visualized as RV DCE in approximately one third to one half of ARVC patients. 16,31,34 Tandri et al 31 first reported RV DCE in 8 (67%) of 12 of patients with ARVC and demonstrated its relation to inducibility of sustained monomorphic VT at electrophysiological testing and fibrofatty myocardial changes at EMB. Sen-Chowdhry et al 16 reported unequivocal RV DCE in 13 (65%) of 20 patients who fulfilled task force diagnostic criteria for ARVC and were desmosomal gene mutation carriers.…”
Section: Rv Dce Findingsmentioning
confidence: 99%
“…Sen-Chowdhry et al 16 reported unequivocal RV DCE in 13 (65%) of 20 patients who fulfilled task force diagnostic criteria for ARVC and were desmosomal gene mutation carriers. Santangeli et al 34 found RV DCE in 8 (53%) of 15 of patients with an ARVC diagnosis based on the task force criteria. The lack of RV DCE in a significant proportion of patients fulfilling the diagnostic criteria of ARVC was explained by early disease variants with a small amount of fibrofatty tissue or even by pure fatty variants of the disease undetectable by DCE techniques.…”
Section: Rv Dce Findingsmentioning
confidence: 99%
“…In extending this correlation to RV regions of delayed gadolinium enhancement hyperenhancement by cardiac magnetic resonance, this work underscores the critical importance of delayed gadolinium enhancement in evaluation of the patient suspected of having ARVC and offers hope for more reliable cardiac magnetic resonance-based diagnosis. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In a study of 17 patients with biopsy-proven disease, abnormalities on the signal-averaged ECG correlated most closely with lowvoltage areas in the right ventricular outflow tract, whereas surface ECG abnormalities were associated with more diffuse right ventricular involvement. 29 Delayed gadolinium enhancement on magnetic resonance imaging was also highly associated with the distribution of low-voltage areas. Percutaneous epicardial mapping has defined electroanatomic correlates of pathological observations, indicating that myocardial involvement in arrhythmogenic cardiomyopathy progresses from epicardium to endocardium.…”
Section: New Ecg and Electroanatomic Features In Arrhythmogenic Cardimentioning
confidence: 99%